Fabrication, Rheology and Antioxidant Activity of Palm Esters-based Emulsions Loaded with Tocotrienol - S.H NG; B Mahiran; I Zahariyah (Universitas Gadjah Mada, 2014)
Palm oil esters are wax esters derived from palm oil and oleyl alcohol. Palm oil esters have many applications due to their luxurious moisturizing properties, non-greasy and blend easily with fragrances and colours when applied on skin surface. The aim of this research was to fabricate palm esters-based emulsions cream for topical delivery, characterise the rheological properties and in vitroantioxidant activity of the palm esters-based emulsions system. Emulsions containing palm oil esters loaded with tocotrienol were obtained in two stages, with propagation of rotor-stator at 6000 r.p.m. for 5 min and further emulsified using an ultrasound at various acoustic amplitudes for another 5 min. A stress/rate controlled Kinexus Rheometer with a temperature controller was used to measure the rheological properties of the emulsion. Rheology measurements were performed at 25.0°C ± 0.1°C with 4°/40 mm cone and plate geometry. Thein vitro antioxidant activity was investigated using UV-Vis spectrophotometer.The yield stress of the emulsions increased with increasing acoustic amplitudes. The viscoelasticity of the emulsions were enhanced by the increase in the oil and surfactant concentrations. The emulsions with higher oil phase concentration [30% (w/w)] showed greater elasticity which implied strong dynamic rigidity of the emulsions. The cohesive energy increased significantly with surfactant concentration especially for the emulsions with 30% (w/w) oil phase concentration. The palm oil esters emulsions containing tocotrienol gave higher Trolox equivalent antioxidant capacity values which implied higher antioxidant capability. The tocotrienol in emulsion with 30% (w/w) dispersed phase showed that they were the most stable with longest shelf life and exhibited greater inhibitory effects on the ABTS